Human Capital Barriers to Technological Absorption and Innovation by Ethiopia’s Micro and Small Enterprises (MSEs) - Belete, Wondwossen (My University, 2015)
Ethiopia’s private sector is dominated by micro and small enterprises (MSEs), many of them operating informally. Accordingly, a key challenge for the country’s science, technology and innovation (STI) policymakers is finding ways to ensure that these small businesses absorb external technological innovations in order to enhance their performance and allow for follow-on innovations. This policy objective has an access to knowledge (A2K) dimension, because Ethiopia’s STI policies and strategies stress the need for improved MSE access to public domain patent information as a means to improving technological absorption. However, research by the Ethiopian Intellectual Property Office (EIPO) has found that despite the efforts of the Ethiopian government to foster small-enterprise absorption of public domain technological information contained in patent documents, MSE take-up of such technology tends to be poor (Belete, 2013). In this piece, the author, former EIPO Director of Intellectual Property Policy and Planning, argues that the government’s emphasis needs to be on building human capital in MSEs, in order to improve their capacity to absorb patent information. This argument draws on literature linking technological absorption capacity to human capital levels, along with findings from an Ethiopian government survey of 3,000 MSEs (MUDC, 2013). The author recommends improved MSE collaboration with intermediary organisations such as the country’s Technical and Vocational Education and Training (TVET) institutions and industry development institutes.
Keywords: Ethiopia, micro and small enterprises (MSEs), innovation, patents, patent information, public domain, intellectual property (IP) rights, access to knowledge (A2K), technological absorption, absorptive capacity, human capital